2011
DOI: 10.1016/j.ijscr.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer presenting with polymyositis—A case report

Abstract: The diagnosis of polymyositis in the elderly population should raise suspicion of an underlying malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…One characteristic of colorectal tumor progression is patient weight reduction and the presence of blood in the stool [27,28]. Body weight decrease is attributed to chronic constipation and abdominal pain whereas bleeding can be caused by the friction and shear of the stool with the projecting interstitial tumors [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…One characteristic of colorectal tumor progression is patient weight reduction and the presence of blood in the stool [27,28]. Body weight decrease is attributed to chronic constipation and abdominal pain whereas bleeding can be caused by the friction and shear of the stool with the projecting interstitial tumors [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Various population-based studies have shown association of colorectal cancer with DM [5,6]. However, its association with PM is limited to few case reports [8][9][10][11]. The diagnosis of cancer can be before, after or simultaneously with myositis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patient history and physical examination are essential components in the diagnosis of gastrointestinal tract tumors. Some of the common symptoms are abdominal pain, abdominal distention, and bloody stool, and the specific symptoms of colorectal cancer are changes in bowel habits and intestinal obstruction [ 12 14 ]. Abdominal examination and digital rectal examination are important tools in the diagnosis of gastrointestinal tract tumors.…”
Section: Discussionmentioning
confidence: 99%